Evaluation of a recombination-resistant coronavirus as a broadly applicable, rapidly implementable vaccine platform. (December 2018) - Graham, Rachel; Deming, Damon; Deming, Meagan; Yount, Boyd; Baric, Ralph
Abstract Emerging and re-emerging zoonotic viral diseases are major threats to global health, economic stability, and national security. Vaccines are key for reducing coronaviral disease burden; however, the utility of live-attenuated vaccines is limited by risks of reversion or repair. Because of their history of emergence events due to their prevalence in zoonotic pools, designing live-attenuated coronavirus vaccines that can be rapidly and broadly implemented is essential for outbreak preparedness. Here, we show that coronaviruses with completely rewired transcription regulatory networks (TRNs) are effective vaccines against SARS-CoV. The TRN-rewired viruses are attenuated and protect against lethal SARS-CoV challenge. While a 3-nt rewired TRN reverts via second-site mutation upon serial passage, a 7-nt rewired TRN is more stable, suggesting that a more extensively rewired TRN might be essential for avoiding growth selection. In summary, rewiring the TRN is a feasible strategy for limiting reversion in an effective live-attenuated coronavirus vaccine candidate that is potentially portable across the Nidovirales order. Rachel Graham et al. show that coronaviruses with extensively rewired transcription regulatory networks are effective vaccine candidates against Severe Acute Respiratory Syndrome Coronavirus. The reversion of live-attenuated vaccine strains to virulence can be avoided with these vaccines.